Implementation of Patient Safety Culture at Hospital X, Semarang City - Muhammad Iqbal; Firmansyah Kholiq Pradana P.H; Vilda Ana Veria Setyawati; Lutfiyah Rizqulloh (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Patient safety incidents remain a persistent challenge in hospital settings, yet evidence on the cultural factors driving them in type C hospitals in Indonesia remains limited. Hospital X in Semarang City recorded 23 patient safety incidents from January to September 2023 (KTD: 2, KTC: 9, KNC: 12), with label dispensing errors, wrong medication, and wrong dosage as the leading causes. Despite the establishment of a Hospital Patient Safety Team (KPRS), no systematic assessment of patient safety culture had previously been conducted, leaving a critical gap in understanding the organizational factors underlying these incidents. This study aimed to determine factors influencing patient safety culture as perceived by nurses at Hospital X. A quantitative cross-sectional design was employed, with 82 inpatient nurses selected via simple random sampling. Data were collected using a validated AHRQ-based questionnaire and analyzed using Chi-square and Fisher's Exact tests. The average positive response to patient safety culture was 81.5%. The highest-scoring dimensions were cooperation within the unit (90.2%), open communication (84.1%), and staffing (84.1%), while cooperation between units (74.4%) and error feedback (76.8%) scored lowest. All 12 dimensions showed significant associations with patient safety culture (p < 0.05). The strongest associations were found in open communication (p = 0.001; OR = 18.9), error feedback (p = 0.001; OR = 27.5), staffing (p = 0.001; OR = 17.1), and patient transition (p = 0.001; OR = 15.2). These findings indicate that inter-unit coordination and structured error feedback are the most critical intervention targets. Hospital management should prioritize implementing a non-punitive incident reporting system, standardized SBAR-based handover protocols, and integrating patient safety competencies into regular clinical supervision to meaningfully reduce preventable incidents.